2019
DOI: 10.17816/ov2019159-71
|View full text |Cite
|
Sign up to set email alerts
|

Acanthamoeba keratitis. Review of literature. Case reports

Abstract: Acanthamoeba keratitis (АК) is a parasitic infectious condition caused by corneal invasion by free-living amoebae. In 86% of cases, AK affects contact lens wearers. Delayed diagnosis and inadequate treatment of this disease leads to development of a severe form of keratouveitis and corneal perforation. Consequently, this group of diseases is one of the causes of visual disability in working-age population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Because of these variations, we used SEM to report the impact of the extract on the morphology of A. castellanii trophozoites and cysts. Skryabina et al 42 reported that the insufficiency of medical therapy frequently occurs due to the scanty absorption of local anti-Acanthamoebic drugs through www.nature.com/scientificreports/ thickened walls. Our findings showed rupture in the operculum and definite pore formation in the cysts treated with the extract, which might facilitate the diffusion and absorption of the extract.…”
Section: Discussionmentioning
confidence: 99%
“…Because of these variations, we used SEM to report the impact of the extract on the morphology of A. castellanii trophozoites and cysts. Skryabina et al 42 reported that the insufficiency of medical therapy frequently occurs due to the scanty absorption of local anti-Acanthamoebic drugs through www.nature.com/scientificreports/ thickened walls. Our findings showed rupture in the operculum and definite pore formation in the cysts treated with the extract, which might facilitate the diffusion and absorption of the extract.…”
Section: Discussionmentioning
confidence: 99%
“…Increased drug dosage is needed to overcome this barrier and become more effective however; using high doses has toxic and side effects. Moreover, the failure rate of medical therapy frequently occurs due to insufficient absorption of topical anti-Acanthamoebic medications through thicken sclera (Skryabina et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Ismail et al (2018) stated that different concentrations of both aqueous and alcoholic extracts of Nigella sativa possessed more potent cysticidal effect on Acanthamoeba cysts with growth inhibition up to 100% compared to chlorhexidine 0.02% which gave growth inhibitory effect ranging from 56 to 80% throughout the experiment. Although chlorhexidine is used as an initial medication for Acanthamoeba keratitis, continued treatment may lead to destruction of the plasma membranes of ocular cells, epithelial ulceration, keratocytes disappearance and impairment in endothelial function (Skryabina et al 2019). Therefore, the importance of these natural agents is related not only for their cysticidal effect but also they may be used as template molecules for the production of novel therapies less toxic and free from side effects.…”
Section: Discussionmentioning
confidence: 99%